PEMBUATAN SHORTENING DARI CAMPURAN RBD STEARIN DENGAN MINYAK INTI SAWIT SECARA GLISEROLISIS MENGGUNAKAN KATALIS ENZIM LIPASE DARI DEDAK PADI - Masyura M. D. (AGRIUM: Jurnal Ilmu Pertanian, 2011)
AbstractGlycerolysis reaction involves intramoleculer and intermolecular exchange of acyl groups among triglicerides resulting in the changes on the physical and chemical  properties of the result triglicerides. Preparation shortening of the mixture of stearin RBD and palm kernel oil  by glycerolysis using lipase enzyme as catalyzed from rice bran, in order to obtain the products that that meets the quality standards of shortening the measurement of melting point analysis was performed. The shortening produced from the mixture of the stearin RBD and palm kernel oil by glycerolysis in the mol ratio of 1:1:4, 2:2:4, 3:3:4 and 4:4:4  the melting poit was 37.2, 38.5, 40.2 and 41.50C respectively, the solid fat content at 400C was 1.80, 2.50, 5.38 and 6.15% respectively. The study indicated that rice bran as source of lipase enzyme can be use as a catalyst by glycerolysis reaction in shortening preparation.Keywords: shortening, rbd stearin, palm kernel oil, glyserolisys, lipase.